Professor, Prize-Winning Poet, Translator: In Honor of Herbert Woodward Martin - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2020)
Professor Herbert Woodward Martin and his family arrived in Pécs thirty years ago, in early September 1990. He earned a Fulbright grant to teach American and African American literature courses to students of the English Department of Janus Pannonius University as the institution was called at that time. Martin was not the first Fulbright scholar in the department but the first African American who, among other subjects, familiarized the English majors with poems published in The Poetry of Black America: Anthology of the 20thCentury, edited by Arnold Adoff and introduced by Gwendolyn Brooks. The anthology contains some poems by Martin too, including “A Negro Soldier’s Viet Nam Diary,” which has heart-wrenching lines about a black soldier facing the loss of innocent lives in a land destroyed by modern weapons, where “Death hangs on the rice” (Martin, “A Negro Soldier’s” 228)